The Effect of Kinesio Taping on the Reduction of Pain in Patients with Carpal Tunnel Syndrome: Meta-Analysis - Setiawan, Cahyo; Tamtomo, Didik Gunawan; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Carpal tunnel syndrome (CTS) is the most common occurrence of nerve compression. Some cases of CTS have chronic symptoms. The most common complaint is "Nocturnal Acroparesthesia", which is tingling pain at night. Physiotherapy interventions can be done to relieve complaints of CTS one of which is the use of Kinesio Taping. This study aimed to analyze the effect of Kinesio taping on the reduction of pain in patients with carpal tunnel syndrome from some previous studies.Subjects and Method: This was a systematic and meta-analysis study. The study used the PICO model as follows Population=Patients with Carpal Tunnel Syndrome, Intervention= Given Kinesio Taping, Comparison= Not Given Kinesio Taping, and Outcome=Reductionof Pain. The articles used in this study were obtained from several databases including PubMed, ScienceDirect, and Google Scholar. The articles were collected in a month. The keywords for searching the articles were as follows: "kinesio taping" OR "kinesio tape" OR "pain" OR "carpal tunnel syndrome" AND "Randomized Controlled Trial". The articles included in this study were full-text articles with a randomized controlled trial study design. The articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3 application.Results: The total of seven articles reviewed in this meta-analysis study was from Turkey, Poland, the Republic of Korea, Egypt, and the USA. The studies showed that giving KT could reduce pain in CTS and it was statistically very significant (Standardized Mean Difference= -1.21; 95% CI= -2.14 to -0.28; p<0.01).Conclusion: Kinesio Taping can reduce pain in Carpal Tunnel Syndrome.Keywords: kinesio taping, reduction of pain, carpal tunnel syndrome.Correspondence: Cahyo Setiawan, Masters Program In Public Health, Sebelas Maret University, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: setiawan.cahyo10@gmail.com.Mobile Phone: 089693257305.Indonesian Journal of Medicine (2021), 06(01): 104-111https://doi.org/10.26911/theijmed.2021.06.01.11.